2012
DOI: 10.4103/0970-0218.99914
|View full text |Cite
|
Sign up to set email alerts
|

Profile of presentation of Human Immunodeficiency Virus infection in North India, 2003-2007

Abstract: Background:Clinico-epidemiological profile of the Human immunodeficiency virus (HIV) epidemic in India is varied and depends on multitude of factors including geographic location. We analyzed the characteristics of HIV-infected patients attending our Immunodeficiency Clinic to determine any changes in their profile over five years.Settings and Design:A retrospective observational study.Materials and Methods:The study sample included all patients with HIV infection from January 1, 2003 to December 31, 2007. Dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Another study from south and north India also reported that 88-90% of the HIV infected females were monogamous. [2223] In our study, we observed pulmonary tuberculosis was the most common OI, followed by candidiasis, cryptosporidial diarrhea, herpes zoster, cryptococcal meningitis and P. jirovecii pneumonia. Remaining 23.6% patients had conditions other than well-recognized OIs.…”
Section: Discussionmentioning
confidence: 66%
“…Another study from south and north India also reported that 88-90% of the HIV infected females were monogamous. [2223] In our study, we observed pulmonary tuberculosis was the most common OI, followed by candidiasis, cryptosporidial diarrhea, herpes zoster, cryptococcal meningitis and P. jirovecii pneumonia. Remaining 23.6% patients had conditions other than well-recognized OIs.…”
Section: Discussionmentioning
confidence: 66%
“…Sulfonamides and trimethoprim (J01E): A spike in April 2006 with rising trend in Segments 4 and 5 could be explained by additional indications like HIV associated opportunistic infections and the rise of multi-drug resistant malaria [26] , [27] .…”
Section: Discussionmentioning
confidence: 99%
“…A recently published profile of new HIV infections in northern India found that a substantial proportion of newly diagnosed patients entered care in the advanced stage of disease (CD4 count <200 cells/mm 3 ). 7 Untreated, HIV disease progression is associated with declining health and reduced quality of life, including increased depression, fatigue, and disrupted sleep. 8 Quality of life has been associated with improved treatment outcomes, for example, high CD4 count and low viral load, 9,10 and thus, is important to maintain.…”
Section: Introductionmentioning
confidence: 99%